Application of manure, nitrogen fertilizer, and EM4 to improve growth and yield of red chili (Capsicum annuum L) on an Alfisol - J A Setiawan; M D Maghfoer; E Nihayati (Journal of Degraded and Mining Lands Management, 2016)
Red chili is commodity of vegetable that has high economic value, but still has low productivity. The objective of this study was to elucidate the effect of goat manure and Urea application with EM4 and to obtain the best dose of combination in order to improve growth and yield of red chili. The study was conducted at Jatikerto-Malang from January to June 2015. The research applied Factorial Randomized Block Design that comprised of two factors by three replications. First factor: Goat manure and Urea, 25% N PKK + 75% N Urea (A1), 50% N PKK + 50% N Urea (A2) and 75% N PKK + 25% N Urea (A3). Second factor: Doses of EM4 0 L/ha(E0), 30 L/ha (E1), 40 L/ha (E2) and 50 L/ha (E3), and one control treatment (100% N Urea). Results of the study showed that combination of 50% N PKK + 50% N Urea and EM4 at levels 30 and 40 L/ha produced the best and optimal plant height, numbers of branches and number of flowers. Separately, application of 25% N PKK + 75% N Urea produced 292.67 fruits per plant, fruits weight per plant 389.08 g per plant and fruits weight per hectare 10.92 t/ha. EM4 at level 30 L/ha showed the best and optimal fruits weight per hectare, 12.27 t/ha. The control showed better growth but not significant compared with combination of 25% N PKK + 75% N Urea with EM4 at level 30 and 40 L/ha. Combination treatment produced number of fruits 26.01%, fruits weight per plant 21.53% and fruits weight per hectare 25.15% higher than control.